The effect of internal ethical context on subjective well-being: The sequential mediation role of socially responsible human resources management and ethical leadership - Dias, Raquel de Ataíde Claudino Roque (2022)
This research aimed to examine whether organizations’ internal ethical context contributes to fostering employees’ subjective well-being (SWB). Socially responsible human resources management (SRHRM) and ethical leadership were also evaluated and were expected to explain the previous relationship through a sequential mediation effect. For this purpose, data were collected through an anonymous questionnaire to a sample of 315 participants from organizations operating in different business sectors. The internal ethical context was assessed using three elements: the existence of an ethics code, the scope, and relevance of the ethics program. Findings revealed that, while the mere existence of an ethics code did not predict SWB, the scope of the ethics program and employees’ perception of its relevance positively influenced SWB. SRHRM, measured by practices regarding training and development, work-life balance, professional career, communication, and diversity attention, has revealed to be a significant mediator between internal ethical context and SWB. Ethical leadership, on its hand, did not show significance mediating the relationship between organizations' ethical context and SWB, but contributed to the chain of effects of the proposed model. The results indicate that organizations’ internal ethical context increases the adoption of SRHRM practices, that support stronger ethical leadership behavior, and, thereby, promotes higher SWB.